3D bioprinting of mature bacterial biofilms for antimicrobial resistance drug testing. (13th September 2019) - Ning, Evita; Turnbull, Gareth; Clarke, Jon; Picard, Fred; Riches, Philip; Vendrell, Marc; Graham, Duncan; Wark, Alastair W; Faulds, Karen; Shu, Wenmiao
Abstract: The potential to bioprint and study 3D bacterial biofilm constructs could have great clinical significance at a time when antimicrobial resistance is rising to dangerously high levels worldwide. In this study, clinically relevant bacterial species including Escherichia coli, Staphylococcus aureus (MSSA), Methicillin-resistant Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa were 3D bioprinted using a double-crosslinked alginate bioink to form mature bacteria biofilms, characterized by confocal laser scanning microscopy (CLSM) and fluorescent staining. Solid and porous bacteria-laden constructs were reproducibly bioprinted with thicknesses ranging from 0.25 to 4 mm. We demonstrated 3D bioprinting of thicker biofilms (>4 mm) than found in currently available in vitro models. Bacterial viability was excellent in the bioprinted constructs, with CLSM observation of bacterial biofilm production and maturation possible for at least 28 d in culture. Importantly, we observed the complete five-step biofilm life cycle in vitro following 3D bioprinting for the first time, suggesting the formation of mature 3D bioprinted biofilms. Bacterial growth was faster in thinner, more porous constructs whilst constructs crosslinked with BaCl2 concentrations of above 10 mM had denser biofilm formation. 3D MRSA and MSSA biofilm constructs were found to show greater resistance to antimicrobials than corresponding two-dimensional (2D) cultures. Thicker 3D E. coli biofilms had greater resistance to tetracycline than thinner constructs over 7 d of treatment. Our methodology allowed for the precise 3D bioprinting of self-supporting 3D bacterial biofilm structures that developed biofilms during extended culture. 3D biofilm constructs containing bacterial biofilms produce a model with much greater clinical relevance compared to 2D culture models and we have demonstrated their use in antimicrobial testing.